Minimally Invasive Surgery of the Foot and Ankle - Maffulli, Nicola; Easley, Mark.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Minimally Invasive Surgery of the Foot and Ankle is a collection of procedures presented by experts and pioneers in foot and ankle surgery who share an interest in developing less invasive methods of treating disorders of the foot and ankle. Procedures described in detail in this text avoid extensive soft tissue dissection and minimize soft tissue complications while affording results equal to those reported using traditional extensile exposures. These less invasive techniques may minimize post-operative stiffness and pain and shorten operative times and hospital stays. The minimally invasive procedures are not discussed in isolation; instead, they are compared and contrasted with open and arthroscopic methods. Moreover, the concise written text is complemented by a generous assortment of useful clinical photos, diagrams, and imaging studies.
Hallux -- Lesser toes -- Hindfoot -- Ankle -- The Achilles tendon.
Keywords: Medicine; Orthopedics; Orthopedic surgery; Sports medicine; Medicine & Public Health; Orthopedics; Surgical Orthopedics; Sports Medicine